2019
DOI: 10.3390/genes10040314
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Identification and Evolution Analysis of Sox Genes in Coturnix japonica Based on Comparative Genomics

Abstract: Coturnix japonica (Japanese quail) has been extensively used as a model animal for biological studies. The Sox gene family, which was systematically characterized by a high-mobility group (HMG-box) in many animal species, encodes transcription factors that play central roles during multiple developmental processes. However, genome-wide investigations on the Sox gene family in birds are scarce. In the current study, we first performed a genome-wide study to explore the Sox gene family in galliform birds. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 98 publications
5
10
0
Order By: Relevance
“…Recent bioinformatic studies aimed to analyse differentially expressed genes, miRNAs and lncRNAs demonstrated the robustness of the results obtained through the integration of different GEO and TCGA datasets, 37,38 encouraged researchers to carry out the real‐time analysis of in‐motion big data, while protecting privacy and security 39 . With the development of sequencing and bioinformatics technology, more and more gene datasets are released on the public platform, we need to sort them out, and analysed them from more angles 27,40,41 . Compared with low‐grade disease, hsa‐miR‐506‐514 cluster, hsa‐miR‐592, hsa‐miR‐199a‐5p were related to the overall survival of the uveal melanoma patients 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent bioinformatic studies aimed to analyse differentially expressed genes, miRNAs and lncRNAs demonstrated the robustness of the results obtained through the integration of different GEO and TCGA datasets, 37,38 encouraged researchers to carry out the real‐time analysis of in‐motion big data, while protecting privacy and security 39 . With the development of sequencing and bioinformatics technology, more and more gene datasets are released on the public platform, we need to sort them out, and analysed them from more angles 27,40,41 . Compared with low‐grade disease, hsa‐miR‐506‐514 cluster, hsa‐miR‐592, hsa‐miR‐199a‐5p were related to the overall survival of the uveal melanoma patients 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, RobustRankAggreg package (RRA method) was designed to sort the multi‐gene lists and adopted to gain the robust DEGs 26 . The pheatmap package is used to visualize the top 20 up‐ and top 20 down‐ DEGs obtained by the six GEO datasets and TCGA‐GBM dataset by RRA method 27,28 …”
Section: Methodsmentioning
confidence: 99%
“…The genomic and protein data of human was downloaded from NCBI (ftp://ftp.ncbi.nlm.nih.gov/ genomes/all/GCF/000/001/405/GCF_000001405.39_G RCh38.p13). Then, we downloaded the HMM file of HMG-box domain with InterPro ID (IPR009071) from Pfam v32.0 [57] and ran HMMER v3.2.1 [58] to obtain the SOX genes from the complete genome with e-value cutoff 1.8e-21 as previously reported [7]. SOX genes were mapped on chromosomes by Idiographica v2.4 [59].…”
Section: Example: Genome-wide Retrieval and Identification Of Sox Genmentioning
confidence: 99%
“…HOX gene family was highly expressed in GBM cancer stem cells compared with parental lines, and HOX-PBX inhibition was a potential therapeutic target for GBM patients [5], and HOXD10 was targeted by hsa-miRNA-23a to inhibit glioma cell invasion [6]. Sex-determining region Y (SRY)-related high mobility group box of genes was abbreviated as SOX genes [7]. Using human glioma-initiating cell (GIC) lines (GIC1 and GIC2) created from anaplastic oligodendroglioma (AO) and GBM, both GIC1 and GIC2 expressed SOX2 and SOX3, and neither GIC line expressed SOX1 [8].…”
Section: Introductionmentioning
confidence: 99%
“…In common carp SOX1A and SOX1B has 1, 1 exon, same in zebrafish but in the case of Nile tilapia SOX1A has only 1 and SOXB total have 7 exons [23] . The full-length cDNA of SOX2 gene is 997 encoded with 315aa having 1 exon, which is highly comparable with CDS of Indian major carps ( Catla catla, Cirrhinus cirrhosis and Labeo rohita ) and nile tilapia such as 936–997 nucleotides sequences with 315, 322 and 404aa [23] , [53] , [54] . Current work identified SOX such as SOX3 to SOX21 genes have diverse range CDS length like 716 to 1373bp, full-length in base pair is 523–3496 and putative protein sequences 147 to 483aa, pI>6, and Weight in Kilodaltons (kDa) ranges are 50, which are highly comparable with earlier reported SOX genes in fish species [23] , [42] , [53] , [55] .…”
Section: Discussionmentioning
confidence: 81%